Development of Multi-sensor Array Electrodes for Measurement of Deeper Muscle Activation - Koike, Yasuharu; Kim, Yeongdae; Stapornchaisit, Sorawit; Qin, Zixuan; Kawase, Toshihiro; Yoshimura, Natsue (Sensors and materials, 2020)
Muscles of the forearm are related to finger motion, and the forearm is divided into the anterior and posterior compartments. The anterior compartment of the forearm is further divided into the superficial, intermediate, and deep layers, and the posterior compartment into the superficial and deep layers. The superficial-layer muscles are related to wrist motion, and the deep-layer muscles to finger motion. Owing to these anatomical features, electromyogram signals from the superficial layer are mixed with those from the deep layer. In this paper, we introduce a system of multi-sensor array electrodes covering the entire forearm. We developed them to estimate muscle activities from not only the superficial layer but also the deep layer. The electrodes were made from conductive fibers and easy to set up. The EMG signals detected by these sensors were examined by independent component analysis.